Arimidelphis sorbinii a new small killer-like dolphin from the Pliocene of Marecchia River (Central eastern Italy) and a phylogenetic analysis of the Orcininae (Cetacea: Odontoceti - BIANUCCI, GIOVANNI (2005)
Arimidelphis sorbinii is a new genus and a new species of Delphinidae (Cetacea, Odontoceti) based on an incomplete skull with right ear bones, mandible, teeth and left forelimb, all from one animal, from the Late Pliocene sediments of Marecchia river (Central Eastern Italy). This specimen had previously been wrongly referred to the fossil species Tursiops osennae. Arimidelphis shows some affinities with killer whale (Orcinus), as the short rostrum, the very strong preorbital process with circular lateral outline, and the very elevated coronoid crest of the mandible. A cladistic phylogenetic analysis points out the belonging of Arimidelphis to Orcininae and particularly to a clade also including the fossil genus Hemisyntrachelus, Orcinus and Pseudorca. The strong rostrum and mandible indicate a trophic adaptation similar to that of the last two genera. Other results of this cladistic analysis are the placement of Orcaella outside the Orcininae, and the position of Grampus near Globicephala, clearly inside the Orcininae. Tursiops and Delphinus (two genera of Delphininae) appear strongly distinct from Orcininae. This new genus confirms the high radiation of delphinids in the Pliocene of the Mediterranean, probably related to the recolonization of this basin after the Messinian salinity crisis.